From Generosity to Sustainability : The Austrian Pension System and Options for its Reform - Thimann, Christian; Koch, Manfred (Washington, D.C. : International Monetary Fund, 1997)
Austria has probably the world's highest pension expenditures relative to its economic size, largely because of the generosity of its pension system. This paper examines the institutional setup of the Austrian pension system and projects its future development based on current policies. The projection results show a swift financial worsening. With the already high level of contribution rates, pension expenditures, and budget transfers, the results underscore the need for reform. Much of this reform can, however, be achieved by maintaining the structure of the system and adjusting some of its key parameters. The paper outlines options for such a reform.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet